2020
DOI: 10.1111/jonm.13011
|View full text |Cite
|
Sign up to set email alerts
|

A SCOPING REVIEW: The role of the nurse manager as represented in the missed care literature

Abstract: For fifteen years, the subject of missed nursing care has been a cause of concern for the profession of nursing and for researchers. Missed care is usually described as necessary patient care which is left undone, or incomplete due to lack of resources. Much of the research to date has focused on which types of care are missed, the structural and organizational antecedents, and the outcomes for patients, nurses and organizations. However, to date, the role of the nurse manager (NM) in relation to missed nursin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 26 publications
3
50
0
Order By: Relevance
“…The different strategies reported as effective in preventing MNC require a redesign of the nurse leadership, over and above that recently underlined (McCauley et al., 2020) in terms of singular competences (e.g. in how to exhibit leadership and adaptability; how to implement quality and safety improvements; Leotsakos et al., 2014).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The different strategies reported as effective in preventing MNC require a redesign of the nurse leadership, over and above that recently underlined (McCauley et al., 2020) in terms of singular competences (e.g. in how to exhibit leadership and adaptability; how to implement quality and safety improvements; Leotsakos et al., 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Previous literature has underlined the relevance of communication among nurses and other members of the staff at the unit level in order to facilitate a transparent climate that could enhance trust in reporting MNC (e.g. McCauley et al., 2020). However, given the systemic nature of MNC, promoting collaboration and cooperation also across units and with the external environment of the hospital, namely with citizens and the professional body, is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Working in an environment with leadership support for nurses led them to report fewer reasons for missed nursing care relative to material and labour resources. Effective leadership and management can also decrease levels of missed nursing care (McCauley et al., 2020). Other studies have also found that the better the perception of labour and material resources, the less frequent the occurrence of missed care (Blackman et al., 2014; Cho et al., 2015; Smith et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies that evaluated relationships between the nurse work environment and omission of care identified that a lower occurrence of missed care can be linked to a better work environment (Carthon et al., 2015; Kim et al., 2018; Lake et al., 2019; Liu et al., 2018; Smith et al., 2017), adequate management and leadership skills (Kim et al., 2018; McCauley et al., 2020), and adequate material and human resources (Kim et al., 2018; Smith et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Frequent predictors identified were the quality of the nurse work environment, teamwork, communication, resource adequacy (staffing and skill mix), workload, patient care needs, safety climate and culture, ethical climate and nurse job satisfaction (Kalisch et al., 2009a, Schubert et al., 2013, Blackman et al., 2018, Cho, Kim, Yeon, You, & Lee, 2015, Griffiths et al., 2018, Palese et al., 2015, Bragadottir, Kalisch, & Tryggvadottir, 2017, and Friese, Kalisch, & Lee, 2013). Interestingly, as evidenced in a scoping review contained in this issue, to date the nurse manager role has been largely absent in the literature on missed or rationed care (McCauley, Kirwan, Riklikiene, & Hinno 2020). This seems an obvious oversight, which fails to take into account the important role of the nurse manager in relation to planning patient care delivery.…”
Section: So What Do We Know Already?mentioning
confidence: 99%